Argonaute-2 protects the neurovascular unit from damage caused by systemic inflammation - Machado-Pereira, Marta (2022)
Funding PPBI—Portuguese Platform of BioImaging, POCI-01-0145-FEDER-022122; FCT—Fundação para a Ciência e Tecnologia, UID/Multi/00709/2013, SFRH/ BD/137440/2018 (MMP), IF/00178/2015/CP1300/CT0001 (RF); FCT—L’Oréal— UNESCO Portugal for Women in Science (RF).